Examining the Influence of Physical Facilities, Customer Complaint Handling and E-service on Customer Switching Intention - Onyeagwara Chukwuemeka O.; Chukwudi I. Njelita (Lembaga Penelitian dan Pengembangan Teknologi dan Rekayasa, Yayasan Ahmar Cendekia Indonesia, 2022)
The main intention of this study was to determine the drivers of customer switching behaviour in the Nigerian road transport industry using firms in the South East. The researchers adopted the cross-sectional survey research method in this study. The questionnaire served as the major instrument for primary data collection. The study focused on the customers of eight road transport firms (ABC, Peace Mass, God is Good Motors ITC, Abia Line, ESTMASS, TRACAS, and EboMass) in the South East of Nigeria. The sample size for the study was 371 customers of the selected transport firms. Thus, three key drivers of customer loyalty were considered in this study including physical facilities, complaint handling system and e-service availability. The study found positive correlation between all the variables and customer switching intention.